mRNA vaccines encoding computationally optimized hemagglutinin elicit protective antibodies against future antigenically drifted H1N1 and H3N2 influenza viruses isolated between 2018-2020 - Allen, James D.; Ross, Ted M. (Frontiers in Immunology, 2024)
The implementation of mRNA vaccines against SARS-CoV-2 has successfully validated the safety and efficacy of the platform, while at the same time revealing the potential for their applications against other infectious diseases. Traditional seasonal influenza vaccines often induce strain specific antibody responses that offer limited protection against antigenically drifted viruses and co-circulating strains within a season, leading to reduced annual vaccine efficacy. Modern advances in viral surveillance and sequencing have led to the development of in-silico methodologies for generating computationally optimized broadly reactive antigens (COBRAs) to improve seasonal influenza vaccines. In this study, immunologically naïve mice were intramuscularly vaccinated with mRNA encoding H1 and H3 COBRA hemagglutinins (HA) or encoding wild-type (WT) influenza HAs encapsulated in lipid nanoparticles (LNPs). Mice vaccinated with H1 and H3 COBRA HA-encoding mRNA vaccines generated robust neutralizing serum antibody responses against more antigenically distinct contemporary and future drifted H1N1 and H3N2 influenza strains than those vaccinated with WT H1 and H3 HA-encoding mRNA vaccines. The H1 and H3 COBRA HA-encoding mRNA vaccines also prevented influenza illness, including severe disease in the mouse model against H1N1 and H3N2 viruses. This study highlights the potential benefits of combining universal influenza antigen design technology with modern vaccine delivery platforms and exhibits how these vaccines can be advantageous over traditional WT vaccine antigens at eliciting superior protective antibody responses against a broader number of influenza virus isolates.